PENGEMBANGAN MEDIA PEMBELAJARAN TRUTH OR DARE PADA MATERI CERITA FIKSI KELAS IV SEKOLAH DASAR - Tyas, Hesty Dwy Wahyuning; Abdul Aziz Hunaifi; Aprilia Dwi Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning media functions as an intermediary or channel or bridge in communication activities (delivery and reception of messages) between communicators (message transmitters or teachers) and communicants (message recipients or students). The aim of this research is develop Truth or Dare card learning media and determine the feasibility and response of students to the learning media developed for learning Indonesian with Fiction Story material in class IV SDN 3 Tiron. This research uses the Research and Development (R&D) development method with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation), with the research subjects being fourth grade students at SDN 3 Tiron. The data collection instruments used were interviews, validation sheets, and student response questionnaires. The validation results obtained from material experts were 94% in the "very valid" category, 88% from media experts in the "very valid" category and 94.2% from practitioner experts in the "very practical" category. The student response results reached 100% which was included in the "very good" interpretation category based on the Likert scale. The validation results from material experts, media and practitioner experts show that the Truth or Dare card learning media is very suitable for use in the learning process. The results of the student response questionnaire showed that students were interested in the Truth or Dare card learning media. Truth or Dare learning media is a game that can be created in groups and can stimulate students to play an active role so that it can be used as a learning solution for fictional story material and by using this learning media students can more easily understand the material that has been presented, this can certainly improve student achievement and with increasing student achievement learning outcomes can also be achieved.